Population genetic structuring in Opisthorchis viverrini over various spatial scales in Thailand and Lao PDR. - Nonglak Laoprom; Paiboon Sithithaworn; Ross H Andrews; Katsuhiko Ando; Thewarach Laha; Sirawut Klinbunga; Joanne P Webster; Trevor N Petney (Public Library of Science (PLoS), 2012)
Khon Kaen Province in northeast Thailand is known as a hot spot for opisthorchiasis in Southeast Asia. Preliminary allozyme and mitochondrial DNA haplotype data from within one endemic district in this Province (Ban Phai), indicated substantial genetic variability within Opisthorchis viverrini. Here, we used microsatellite DNA analyses to examine the genetic diversity and population structure of O. viverrini from four geographically close localities in Khon Kaen Province. Genotyping based on 12 microsatellite loci yielded a mean number of alleles per locus that ranged from 2.83 to 3.7 with an expected heterozygosity in Hardy-Weinberg equilibrium of 0.44-0.56. Assessment of population structure by pairwise F(ST) analysis showed inter-population differentiation (P<0.05) which indicates population substructuring between these localities. Unique alleles were found in three of four localities with the highest number observed per locality being three. Our results highlight the existence of genetic diversity and population substructuring in O. viverrini over a small spatial scale which is similar to that found at a larger scale. This provides the basis for the investigation of the role of parasite genetic diversity and differentiation in transmission dynamics and control of O. viverrini.